PENGARUH INFLUENCER MARKETING, PROMOSI, DAN CITRA MEREK TERHADAP MINAT BELI PRODUK SKINCARE SKINTIFIC DI KOTA PONOROGO - Oktavia, Ayu; Dianasari, Mila; Rahmawati, Rizqi (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This study aims to analyze the influence of influencer marketing, promotion, and brand image on purchase intention of Skintific skincare products in Ponorogo City. Influencer marketing, promotion, and brand image are considered important factors that affect consumer purchase intention when choosing skincare products. This research employs a quantitative method with a survey approach, in which data were collected through questionnaires distributed to 80 respondents who are consumers of Skintific skincare products in Ponorogo City. Data analysis was conducted using multiple linear regression to examine the effect of the three independent variables on the dependent variable. The results show that influencer marketing has a positive and significant effect on purchase intention, promotion has a positive and significant effect on purchase intention, and likewise, brand image has a positive and significant effect on purchase intention. These findings indicate that effective influencer marketing, attractive promotion, and a strong brand image can enhance consumers’ purchase intention toward Skintific skincare products in Ponorogo City. The study also found that brand image has the most dominant influence on purchase intention. Therefore, the company should pay greater attention to other variables such as influencer marketing and promotion, as they also play an important role in influencing consumers' intention to purchase Skintific skincare products.